Application of multi-resolution modelling in emergency evacuation simulation. (1st January 2012) - Yang, Bo; Wu, Yong-gang; Ren, Bo
It is an important field to lucubrate the crowd dynamic in evacuation and its simulation in computer. This will help to optimise building structure, produce effective management procedures for emergency egress, prevent and reduce human loss in emergency evacuation. The research of evacuation modelling and simulation is widely developed with the development of computer simulation. The theory and method of multi-resolution modelling provide a new way to simulate the crowd dynamics. In this paper, two kinds of resolution model on pedestrian evacuation and simulation have been presented. One is based on multi-agent framework and a modified PSO algorithm. The other is based on the Euler equations of fluid dynamics. The case study of pedestrian flow simulation in Optical Valley Plaza is explored thoroughly by using the fluid dynamic equation. The aggregate/disaggregate algorithm of multi-resolution model is presented to implement the interaction and parallel computing of the micro simulation model and the macro simulation model. The problem of consistency maintenance when multi-resolution models are parallel implemented is researched and a new algorithm is proposed.